Reactivation of silent rRNA genes by simian virus 40 in human-mouse hybrid cells. - Soprano, K J (1979)
Mouse-human hybrid cells were used to study the ability of simian virus 40 to regulate the expression of rRNA genes in vivo. In these hybrid cells, only the rRNA genes of the dominant species are expressed; the genes for the rRNA of the recessive species are silent. Simian virus 40 infection of these hybrids led to the production of two distinct 28S rRNA species as analyzed by agarose/2.4% polyacrylamide gel electrophoresis. These species were identified as human and mouse rRNAs. This result was confirmed by histochemical studies which indicated that the nucleolus organizer regions of both mouse and human chromosomes were actively synthesizing rRNA in the virus-infected hybrid cells. These results indicate that simian virus 40 infection can induce the expression of otherwise silent rRNA genes.